Language, Policy and Territory A Festschrift for Colin H. Williams - McLeod, Wilson; Dunbar, Rob.; Jones, Kathryn; Walsh, John. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This volume celebrates the contribution of Professor Colin Williams, an immensely important and influential scholar in the field of language policy for more than forty years. Eighteen chapters by former students, colleagues and collaborators address a range of topics involving different aspects of language legislation and language rights, governance, economics, territoriality, land use planning, and onomastics. Six chapters address policy issues in Professor Williams's native Wales while others focus on Canada, Catalonia, Ireland and Scotland. The volume concludes with an Afterword by Professor Williams himself. The book will be suitable for postgraduates and researchers not only in the field of language policy and planning but also sociolinguistics, geography, law and political science. Wilson McLeod is Professor of Gaelic at the University of Edinburgh, UK. Author of Gaelic in Scotland: Policies, Movements, Ideologies (2020) and co-editor of Language Revitalisation and Social Transformation (Palgrave Macmillan, 2021). Robert Dunbar is Professor of Celtic at the University of Edinburgh, UK. He has published widely on language law and policy, and is regularly consulted by international organisations, governments and NGOs on these issues. Kathryn Jones is Managing Director of IAITH: Y Ganolfan Cynllunio Iaith / Welsh Centre for Language Planning. She is co-editor of Multilingual Literacies: Reading and Writing Different Worlds (2001). John Walsh is Senior Lecturer in Irish at the National University of Ireland, Galway, Ireland. He is co-author with Bernadette O'Rourke of New Speakers of Irish in the Global Context: New Revival? (2020).
1. Introduction -- Part I: Theorising language policy and regulation -- 2. Language policy as a form of public policy -- 3. Language rights, human rights and the right to chat -- 4. Language and space: a new research agenda for urban geolinguistics -- 5. Reflections on language as a vehicle of economic value -- Part II: Language policy challenges in Wales -- 6. Language planning in Wales: Joining the dots -- 7. Recent legal developments in Wales: moving beyond individual to group rights? -- 8. Networked territories of language and nation -- 9. Placemaking: towards rethinking land-use planning and language planning for a thriving -- 10. Signs of the times: Onomastics and language policy in Wales -- 11. Canolfannau Cymraeg - a top-down or bottom-up approach to language planning? -- Part III: Language policy challenges in Canada -- 12. Best practices and language policy designs: lessons from Canada and Wales -- 13. F.R. Scott and the origins of language policy in Canada -- 14. The uncertain future of French in Canada -- 15. The planned decline of the English school system in Quebec -- Part IV: Language policy challenges in Ireland, Scotland and Catalonia -- 16. Changing spaces: the new geographies of the Gaeltacht and Irish language networks -- 17. Lessons learned, lessons ignored: The continuing road to an Irish Language Act in Northern Ireland -- 18. The influence of Wales on policies for Gaelic in Scotland -- 19. 'Volunteering for the language in Catalonia' (VxLl): more than a space for linguistic mudes -- 20. Afterword.
Keywords: Language policy; Philology; Sociolinguistics; Political planning; Human geography; Cultural geography; Language Policy and Planning; Languages; Sociolinguistics; Public Policy; Social and Cultural Geography